The sense of presence: lessons from virtual reality - Erickson-Davis, Cordelia (Religion, brain & behavior, 2021)
The sense of presence—or the sense of “being there”—is a poorly understood phenomenon, especially in the case of “unseen others,” e.g., God. We used the tools of virtual reality (VR) to explore the effects of active imagination in creating a sense of presence of an ambiguously real other. We found that adding a visual representation was more effective than verbal language alone in evoking a sense of social presence in a ten-minute intervention, that a proclivity for absorption enhanced the sense of social and environmental presence, and that a sense of social presence was associated with a sense of responsive interaction. We present our data together with a critical analysis of the literature on perceptual presence and conclude by suggesting that presence is best understood as the product of a collaboration between a perceiving subject and the environment within which they are embedded. This study serves as an example of a novel approach that bridges different scientific literatures, methods, and disciplines to study religious experience.